1949
DOI: 10.1111/j.1151-2916.1949.tb19766.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Erosion of Nozzles in Open‐hearth Ladles*

Abstract: A detailed report is presented of experiments made with removable nozzle extensions to determine the relative amount of erosion when various types of steel are teemed through (I) regular fire-clay nozzles fired to different temperatures and ( 2 ) nozzles of the more refractory types. The mechanism of erosion is discussed. The data indicate the limitation of refractory materials having a P.C.E. of 28 or higher for use in nozzles or as open-hearth ladle brick.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1960
1960
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…[8][9][10][11][12] Several of the deposited inclusions are located at typical zones of the nozzle promoting the deleterious clogging phenomenon. [13][14][15][16][17][18][19][20][21] Other authors have studied the fluidynamics inside the nozzle trying to figure out the inclusion deposition at the typical adhesion zones, finding that these are related to low pressure and high turbulence zones. [22][23][24][25][26] In contrast, many researchers have tried to establish the variables affecting the inclusion trajectory, focusing on the forces balance.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Several of the deposited inclusions are located at typical zones of the nozzle promoting the deleterious clogging phenomenon. [13][14][15][16][17][18][19][20][21] Other authors have studied the fluidynamics inside the nozzle trying to figure out the inclusion deposition at the typical adhesion zones, finding that these are related to low pressure and high turbulence zones. [22][23][24][25][26] In contrast, many researchers have tried to establish the variables affecting the inclusion trajectory, focusing on the forces balance.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers [1][2][3][4][5][6][7][8][9][10][11][12][13][14] investigated the clogging behavior and obtained valuable information. Clogging was classified into four types by Thomas et al 1,2) according to its origins: deoxidation products, solidified steel, complex oxides and reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators analyzed the composition of clogging during the casting of aluminum-killed steel, and found that alumina was the main phase. Some of them concluded that these alumina inclusions formed by deoxidation were the main reason for clogging, [3][4][5][6][7] while some found that the reaction between the steel and the nozzle refractory could also cause clogging. [8][9][10][11] Besides, reoxidation were also considered as a source of clogging.…”
Section: Introductionmentioning
confidence: 99%
“…In 1949, Snow and Shea found Al 2 O 3 covering the bore surface of nozzles used to teem Al-killed steel ingots. [210] Duderstadt et al [211] found that nozzle blockage contained high levels of Al (0.0036 pct) and that nozzle sectioning revealed dendritic growth of alumina from the nozzle wall onto the bore. Farrell and Hilty [212] observed clogs of Al, Zr, Ti, and rare earth metals.…”
Section: Inclusion Agglomeration and Clogging During Steel Pouringmentioning
confidence: 99%